Artificial Intelligence Research in Education: A Bibliometric Analysis - Rozali Ilham; M. Giatman; Hasan Maksun (Journal on Education, 2024)
The Importance of Artificial Intelligence cannot be ignored in this era. Artificial Abilities intelligence to process data quickly and accurately allows us to make more informative and intelligent decisions. In the education sector, Artificial intelligence has opened up new opportunities in enhancing the learning experience. The aim of this research is to determine publication trends related to Artificial intelligence in education in the last decade. Data is taken from the database Scopus which was then refined through 4 stages. Method used is method analysis bibliometrics. Research results show that amount publication related Artificial intelligence in continuing education increase since 2014 to in 2022. Analysis of research focus reveals three main clusters in Artificial research intelligence in education, each reflecting a focus on the use of Artificial intelligence in general learning, medical education, and higher education. This information helps researchers and policy makers to understand the dominant trends in research and allocate resources wisely. The emergence of new keywords such as chat gpt shows that Artificial intelligence continues to develop in education. This creates new opportunities for research and development in this area, which researchers and practitioners need to engage in to remain relevant.